The concept of establishing a Syariah supervisory committee in Malaysian hospitals - Samsudin, Muhammad Adib; Mohd Kashim, Mohd Izhar Ariff; Yahaya, Mohammad Zaini; Ismail, Ahmad Munawar; Mohd Khalid, Rozida; Laluddin, Hayatullah; Mohd Sobri, Irwan; Syed Sulaiman, Syed Azhar (Elsevier, 2015)
A review of the literature has shown that several aspects of hospital management in Malaysia do not comply with Islamic laws, for example, the choice of drugs and medical personnel-patient relationship of different gender. These two important issues need to be addressed wisely and discreetly in order to preserve Malaysia's status as an Islamic country. The first issue, regarding the choice of drugs, mean that at times there is confusion and doubt on the halal status of certain drugs. For example, the allergy drug Red Tab Clartine and Ultratab Tablet Benadryl were reported to contain by-product that were of porcine and bovine origin. the second issue, which is the mu'amalah between a medical personnel and patient of different gender, arises specially in cases of expecting mothers. Most were uncomfortable when male doctors handled the delivery process. These two issues have been a concern for Muslims and the reason why Muslim religious scholars(ulamas) have stressed the importance of consuming halal drugs (if available), and to be aware of boundaries between genders including the medical personnel-patient relationship. Thus, for the benefit of the Muslim, who are the majority in Malaysia, this conceptual article will debate the rationale of establishing a syariah supervisory committee in Malaysian hospitals, especially in dealing with modern biotechnology products. This paper will also look at some models that oversee the ethics of pharmaceutical management and medical personnel-patient relationships that are related with the proposed establishment of a syariah supervisory committee.